2021
DOI: 10.1097/pra.0000000000000546
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Predatory Behavior in an Adolescent Female

Abstract: This report describes a rare case of an adolescent female with a history of unspecified depressive disorder, disinhibited social engagement disorder, and significant history of sexual trauma at an early age, who initially presented with suicidal ideation. During the initial evaluation, the patient was found to have engaged in sexually predatory behavior toward younger boys, including solicitation and inappropriate sexual behavior. This report discusses relevant literature on the prevalence, risk factors, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The 3 cases presented in this issue [1][2][3] highlight diagnostic challenges faced when evaluating adolescents, in particular those presenting with a constellation of symptoms including hallucinations. All 3 cases also raise the question of the accuracy of patient report and the importance of further exploration of symptoms before rushing to a diagnosis or treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The 3 cases presented in this issue [1][2][3] highlight diagnostic challenges faced when evaluating adolescents, in particular those presenting with a constellation of symptoms including hallucinations. All 3 cases also raise the question of the accuracy of patient report and the importance of further exploration of symptoms before rushing to a diagnosis or treatment.…”
mentioning
confidence: 99%
“…Deesing et al2 present the case of a 14-year-old girl who presented with depressive symptoms, suicidal ideas, and auditory and visual hallucinations of Satan. Further investigation revealed that the patient had engaged in sexually predatory behavior before admission and in the past.…”
mentioning
confidence: 99%